2015
DOI: 10.1134/s0023158415040096
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative condensation of methane in the presence of modified MnNaW/SiO2 catalysts

Abstract: The effects of cationic (Ce, Zr, and La) and anionic (S, P, and Cl) admixtures on the activity and physicochemical properties of MnNaW/SiO 2 were studied in order to optimize the composition of a catalyst for the oxidative condensation of methane (OCM). It was found that OCM process characteristics can be reg ulated by varying the type (Ce, Zr, La, S, P, and Cl) and concentration (0.5-5 wt %) of a modifying admix ture. For the modified MnNaW/SiO 2 catalysts, the yield of the target reaction products increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…100 mg catalyst diluted in 1.5 ml quartz sand and the feed gas composition of CH 4 :O 2 :N 2 = 4:1:4 was used for the experiments. [20,29,31,32,38,43], it has been also presented similar or lower C 2 yield values (5-16%) in some publications [28,33,48,49]. The scattering in catalytic activity results can be clearly seen in Figure 12 However the reason of this fact can be explained that catalytic activity results for the OCM depends strongly on the different factors, e.g.…”
Section: Catalysismentioning
confidence: 70%
“…100 mg catalyst diluted in 1.5 ml quartz sand and the feed gas composition of CH 4 :O 2 :N 2 = 4:1:4 was used for the experiments. [20,29,31,32,38,43], it has been also presented similar or lower C 2 yield values (5-16%) in some publications [28,33,48,49]. The scattering in catalytic activity results can be clearly seen in Figure 12 However the reason of this fact can be explained that catalytic activity results for the OCM depends strongly on the different factors, e.g.…”
Section: Catalysismentioning
confidence: 70%
“…The multi-length-scale chemical CT experiments presented in this study showed that the La can play this role by trapping the mobile/volatile Na + and WO4 2species by forming this new crystalline phase (NaLa(WO4)2). More importantly, these new results is a major breakthrough in the OCM catalyst design; not only the integrity of catalyst is maintained during the operating conditions but also the catalyst activity is not impaired by the addition of the La components 32,33 . The latter could be attributed to the fact that the OCM reaction process is generally accepted to be based on methane activation at the catalyst surface and gas-phase recombination of methyl radicals.…”
Section: Discussionmentioning
confidence: 99%
“…Ghose et al achieved 27 % C2 yield, one of the highest reported values for fixed bed reactors in literature, using a 5 % La-10 % Na2WO4-5 % Mn/SiO2 catalyst 32 . More importantly, the presence of La was shown to provide a higher performance of Mn-Na-W/SiO2 catalyst in the OCM reaction as well as improve its stability 32,33 . However, it is still not clear how the La promoter leads to this enhancement in catalyst performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that modification of supports is an effective way to control the catalyst performance in reforming of fuels [24][25][26][27][28][29][30]. This study is devoted to the elucidation of the role of support composition in autothermal reforming of ethanol over Ni/Ce 1-x Gd x O y , Ni/Ce 1-x La x O y and Ni/Ce 1-x Mg x O y catalysts.…”
Section: Introductionmentioning
confidence: 99%